Persepsi Masyarakat Terhadap Perubahan Budaya di Tana Toraja (Studi Kasus Upacara Rambu Tuka’) - Rahmad, Abdul (UNIVERSITAS NEGERI MAKASSAR, 2018)
The purpose of this study is to find out: 1) what factors influence the shift in the values of the Rambu Tuka 'ceremony in Toraja, and 2) to find out how the cultural values of Rambu Tuka' in the Toraja are shifted. This study aims to determine what factors influence the shift in the values of the Rambu Tuka 'ceremony in Toraja. Knowing the shift in the cultural values of Rambu Tuka 'in Toraja. The collection of data using the method of observation, interviews and documentation. So that the results of the study show that out of all the results outline the factors that cause cultural changes in Toraja are caused by many factors. Factors that greatly influence the shift in cultural values of tuka signs in tana toraja are; Modern technology, and other cultural influences. So from that it can be concluded that the public perception of the cultural changes that exist in Toraja, is not much different from each respondent's opinion. For the generations of Toraja youth, Let us maintain the culture that has developed in the community such as the Ruka Tuka 'ceremony, so that values contained such as togetherness, help, and cooperation are maintained considering that one of the great potentials for tourism is in the culture of Tana Toraja